Preparation and Mechanical Properties of Graphene Reinforced Poly(vinyl alcohol) Nanocomposites - Wang, Chunyan; Wu, Hongfu; Qian, Yong (Asian Journal of Chemistry, 2015)
The incorporation of carbon nanomaterials significantly affected the macroscopic properties of the polymer-based composites. In this paper, graphene oxide nanosheets which exhibited excellent dispersibility and compatibility in poly(vinyl alcohol) matrix were successfully incorporated into poly(vinyl alcohol) through solution mixing; the mechanical properties and reinforced mechanism were investigated in detail. A 52.3 % increase in the tensile strength and a 94.2 % improvement in the Young's modulus were achieved for 2 wt. % graphene oxide loading. The success of this method provides a good rational for developing high-performance poly(vinyl alcohol)-based composite materials.